Varicella and Cerebral Infarction - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
A relation between varicella and idiopathic arterial ischemic stroke in children was determined in a case control study at the Universite Catholique de Louvain, Brussels, Belgium, and the Centre Hospitalier Bicetre, France.